2017
DOI: 10.1080/19336896.2017.1367082
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant alterations of the expressions and S-nitrosylation of calmodulin and the downstream factors in the brains of the rodents during scrapie infection

Abstract: The aberrant alterations of calmodulin (CaM) and its downstream substrates have been reported in some neurodegenerative diseases, but rarely described in prion disease. In this study, the potential changes of Ca/CaM and its associated agents in the brains of scrapie agent 263K-infected hamsters and the prion infected cell line SMB-S15 were evaluated by various methodologies. We found that the level of CaM in the brains of 263K-infected hamsters started to increase at early stage and maintained at high level ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Our previous dynamic studies suggest that CaM levels in the brain tissues of scrapie‐infected rodents rise rapidly then plateau at a relatively early stage of the disease [10]. In line with this observation, we also identified a significant association between the interval from onset to sampling and the rate of CSF CaM positivity via a single‐factor analysis.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our previous dynamic studies suggest that CaM levels in the brain tissues of scrapie‐infected rodents rise rapidly then plateau at a relatively early stage of the disease [10]. In line with this observation, we also identified a significant association between the interval from onset to sampling and the rate of CSF CaM positivity via a single‐factor analysis.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous study demonstrated that brain CaM levels in scrapie‐infected mouse models are markedly increased [10]. To assess the potential changes in CSF CaM levels in probable sCJD, two types of pooled CSF samples from three patients with probable sCJD and three patients with non‐PrDs were subjected to CaM‐specific Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the representive biomarkers of ER stress, the levels of protein disulfide isomerase (PDI) and Grp78 abnormally up-regulated in the cells expressing PrP mutants and in the brains of scrapie-infected rodents, accompanying with aberrant S-nitrosylated modification [26]. A number of factors involving in Ca 2+ homeostasis, such as calmodulin (CaM) [27] and calpain [28], are also abnormally changed in the brain tissues of prion infection and in the cells expressing PrP mutants. In this study, we provide the evidence that RyR2, the ER-resident Ca 2+ channel, decreases remarkably in the cell line supporting prion replication and in the brain collected from scrapie infected mice and the patients of various types of human prion diseases.…”
Section: Discussionmentioning
confidence: 99%